Video game storytelling : what every developer needs to know about narrative techniques - Skolnick, Evan. (Berkeley : Watson-Guptill, 2014)
"This handy, to-the-point reference guide for video game development emphasizes the significance of storytelling and writing skills for creating today's most popular, narratively-engrossing video games. Video Game Storytelling provides developers with comprehensive, but easy-to-follow advice for facilitating the creation of compelling storylines in today's most popular and narratively successful video games. Video game writer and game writing instructor Evan Skolnick offers a clear and concise development reference guide for aspiring and professional developers, showing how each role (from character designer to animator to audio engineer and more) is impacted by and can affect the story/narrative of a game. This book aims to instill an understanding and appreciation of the basic storytelling principles that are essential for producing truly memorable video games that will bring today's savvy gamers back time and time again"--
Keywords: Video games -- Design; Storytelling; GAMES / Video & Electronic; COMPUTERS / Programming / Games; ART / Digital